X‐linked hypophosphatemic rickets: Case report of late diagnosis and bone pain improvement with targeted treatment - Marcia Janneth Bermeo Cabrera; Pablo Roberto Ordoñez Chacha; Alfredo Adolfo Reza‐Albarrán; Ana Karina Ordoñez Chacha; Marcy Acosta Acero; Agustin Rodas Serrano (Clinical Case Reports, 2022)
Abstract X‐linked hypophosphatemia (XLH) is a rare disexase in which patients present with severe bowing of the legs, joint pain, and mobility problems. XLH has major adverse repercussions on the quality of life.